Pengaruh Transformasi Digital Dan Pengembangan Financial Technology (Fintech) Terhadap Inovasi Layanan Perbankan Syariah - Amanda Taskia Rahmah; Iqbal Fasa, Muhammad (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
Digital transformation and developments in financial technology (fintech) have changed the global banking landscape, including sharia banking. In the Islamic banking sector, digital transformation and fintech present great opportunities to increase efficiency, reach and quality of service. The method used in this research is a qualitative method by collecting secondary data from various related sources. The research results show that the adoption of digital technology and innovation in fintech has increased efficiency, accessibility and quality of banking services and attracted customer interest. Fintech expands access to sharia financial services, increases operational efficiency and encourages product development such as mobile banking and digital payments.